Using slaughterhouse waste in a biochemical-based biorefinery - results from pilot scale tests - Schwede, Sebastian (Environmental technology, 2017)
A novel biorefinery concept was piloted using protein-rich slaughterhouse waste, chicken manure and straw as feedstocks. The basic idea was to provide a proof of concept for the production of platform chemicals and biofuels from organic waste materials at non-septic conditions. The desired biochemical routes were 2,3-butanediol and acetone-butanol fermentation. The results showed that hydrolysis resulted only in low amounts of easily degradable carbohydrates. However, amino acids released from the protein-rich slaughterhouse waste were utilized and fermented by the bacteria in the process. Product formation was directed towards acidogenic compounds rather than solventogenic products due to increasing pH-value affected by ammonia release during amino acid fermentation. Hence, the process was not effective for 2,3-butanediol production, whereas butyrate, propionate, γ-aminobutyrate and valerate were predominantly produced. This offered fast means for converting tedious protein-rich waste mixtures into utilizable chemical goods. Furthermore, the residual liquid from the bioreactor showed significantly higher biogas production potential than the corresponding substrates. The combination of the biorefinery approach to produce chemicals and biofuels with anaerobic digestion of the residues to recover energy in form of methane and nutrients that can be utilized for animal feed production could be a feasible concept for organic waste utilization